(3ObGFb GdMbGFb, aj GdOQL hGdObGFbs - (3GdOeTbqj GdeGpQOjfj, SHW GdeGQOjfj, HOQ GdOjf (B- (3GdZRGd, eMeO Hf eMeO Hf CMeO, (B912 (3g`s
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf djS aj MSGH GdCYeGd GdadcjI CMSf ef WQjb MSGH GdfSHI GdSJjfjI hgj GeSJYedI aj YUQfG gPG hJQchG WQjbI GdCbOejf dUYhHJgG hcKQI GYeGdgG s
(3BNQgG (B:s
(3hWQjbJg Cf JVQH Jdc GdRjGOI Ch GdfbU GdJj Hjf GdeaQhVI hHjf eG jbGQHgG ef GdLOhd aj JaGVd GYOGO GdWhd hGbSe GdMGUd Ydi aVd eG Hjf GdHjJjf CYfj Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\54s
(3cTa GdXfhf (B2\1489s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs